Addendum to "Impressed sources and fields in the volume-integral-equation formulation of electromagnetic scattering by a finite object: A tutorial" [J. Quant. Spectrosc. Radiat. Transfer 214 (2018) 158–167]. (November 2018) - Yurkin, Maxim A.; Mishchenko, Michael I.
Highlights: Electromagnetic scattering by an arbitrary finite object with impressed currents. Compact operator calculus for specific far-field limits. Far-field and mixed reciprocity relations. Abstract: Our recent tutorial referred to in the title has summarized a general theoretical formalism of electromagnetic scattering by an arbitrary finite object in the presence of arbitrarily distributed impressed currents. This addendum builds on the tutorial to provide a streamlined discussion of specific far-field limits and the corresponding reciprocity relations by introducing appropriate far-field operators and linear maps and deriving the reciprocity relations through the pseudo adjoint of these maps. We thereby extend the compact operator calculus used previously to consider the fields and sources near or inside the scattering object.